![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) ( 6x - 84) : 2 - 72 = 201
( 6x - 84) : 2=201+72
( 6x - 84) : 2=273
6x - 84=273x2
6x - 84=546
6x=546+84
6x=630
x=630:6
x=105
b) ( 3x - 34 ) . 63 = 65
3x - 34=65:63
3x - 34=62
3x-81=36
3x=36+81
3x=117
x=117:3
x=39
a) ( 6x - 84) : 2 - 72 = 201
=> (6x - 84) : 2 = 273
=> 6x - 84 = 546
=> 6x = 630
=> x = 105
b) ( 3x - 34 ) . 63 = 65
=> 3x - 34 = 65 : 63 = 62 = 36
=> 3x = 36 + 34 = 36 + 81 = 117
=> x = 39
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,3^n=3^4\)
\(\Rightarrow n=4\)
\(b,2008^n=2008^0\)
\(\Rightarrow n=0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
A, 89 -(73-x)=20
=> 73 - x = 89 - 20
=> 73 - x = 69
=> x = 73 - 69
=> x = 4
B, 7x - 2x = 617:615 + 44:11
=> ( 7 - 2 ) x = 36 + 4
=> 5x = 40
=> x = 8
C, x - [ 42+(-28)]=-8
=> x - 14 = - 8
=> x = - 8 + 14
=> x = 6
D, 62 - (2x-3):3=23
=> ( 2x - 3 ) : 3 = 62 - 23
=> ( 2x - 3 ) : 3 = 39
=> 2x - 3 = 117
=> 2x = 120
=> x = 60
E, 4(x-3)=72 - 110
=> 4 ( x - 3 ) = 49 - 1
=> 4 ( x - 3 ) = 48
=> x - 3 = 12
=> x = 15
\(\frac{x^{n+1}}{6}=6^2\)
\(\frac{x^{n+1}}{6}=36\)
\(\frac{x^{n+1}}{6}=\frac{216}{6}\)
\(x^{n+1}=216\)
\(x^{n+1}=6^{3^{ }}\)
=> x = 6
Vậy x = 6